Sistem Pendukung Keputusan Pemilihan Sufor Untuk Balita Menggunakan Metode VIKOR dan ELECTRE - Saputri, Nur Azizah Indah; Kaesmetan, Yampi R (Jurnal Manajamen Informatika Jayakarta, 2025)
Proper nutrition is crucial for supporting the growth and development of toddlers, especially during the golden age, a critical period for building their fundamental abilities. One alternative source of nutrition besides breast milk is formula milk (SUFOR), which plays a significant role in meeting toddlers' nutritional needs. However, the wide variety of formula milk products with different nutritional contents, prices, and characteristics often makes it difficult for consumers, especially mothers, to choose the best option.This study aims to develop a Decision Support System (DSS) using the VIKOR and ELECTRE methods to assist consumers in selecting the best formula milk. The VIKOR method is applied to determine a compromise ranking by considering both the maximum and minimum utility values of each alternative. Meanwhile, the ELECTRE method compares alternatives pairwise based on predefined criteria to identify the most suitable choice. The selection criteria include nutrition, price, product availability, consumer reviews, packaging, and flavor variations.Data collection involves observations in several milk stores in Kupang City and relevant literature studies. The system is designed using PHP, MySQL, and Visual Studio Code to develop a web-based application with two user roles: admin and user. This system not only helps consumers make informed decisions but also raises awareness about the importance of formula milk nutrition. Ultimately, it is expected to contribute to improving toddlers' nutritional status and reducing stunting and wasting rates in Indonesia.